SorGSD: a sorghum genome SNP database. Issue 1 (December 2016) - Luo, Hong; Zhao, Wenming; Wang, Yanqing; Xia, Yan; Wu, Xiaoyuan; Zhang, Limin; Tang, Bixia; Zhu, Junwei; Fang, Lu; Du, Zhenglin; Bekele, Wubishet; Tai, Shuaishuai; et al.
Abstract Background Sorghum (Sorghum bicolor ) is one of the most important cereal crops globally and a potential energy plant for biofuel production. In order to explore genetic gain for a range of important quantitative traits, such as drought and heat tolerance, grain yield, stem sugar accumulation, and biomass production, via the use of molecular breeding and genomic selection strategies, knowledge of the available genetic variation and the underlying sequence polymorphisms, is required. Results Based on the assembled and annotated genome sequences ofSorghum bicolor (v2.1) and the recently published sorghum re-sequencing data, 62.9 M SNPs were identified among 48 sorghum accessions and included in a newly developed sorghum genome SNP database SorGSD (http://sorgsd.big.ac.cn ). The diverse panel of 48 sorghum lines can be classified into four groups, improved varieties, landraces, wild and weedy sorghums, and a wild relativeSorghum propinquum . SorGSD has a web-based query interface to search or browse SNPs from individual accessions, or to compare SNPs among several lines. The query results can be visualized as text format in tables, or rendered as graphics in a genome browser. Users may find useful annotation from query results including type of SNPs such as synonymous or non-synonymous SNPs, start, stop of splice variants, chromosome locations, and links to the annotation on Phytozome (www.phytozome.net ) sorghum genome database. In addition, general information related to sorghum research such as online sorghum resources and literature references can also be found on the website. All the SNP data and annotations can be freely download from the website. Conclusions SorGSD is a comprehensive web-portal providing a database of large-scale genome variation across all racial types of cultivated sorghum and wild relatives. It can serve as a bioinformatics platform for a range of genomics and molecular breeding activities for sorghum and for other C4 grasses.